Preservice Teachers Engage Parents in At-Home Learning: "We Are in This Together!" - Lori McKee; Anne Murray-Orr; Evan Throop Robinson (University of Windsor, 2022)
During pandemic school closures, preservice teachers designed activity plans to support the at-home learning of children in early elementary grades and recognized parents as vital to supporting their children's learning. This article uses data from a multiple case study of preservice teachers' planning during an alternate practicum. Drawing on models of family vibrancy and parent engagement that arise from funds of knowledge and parent knowledge theories, we highlight how preservice teachers included parents in reciprocal and democratic ways that honoured diverse family's contexts and their knowledge of their children. Results illustrate the importance of asset-oriented, flexible pedagogies that include meaningful parent partnerships both during and beyond the pandemic.